Why Disciplinary Literacies Belong in the Primary Grades: Reviewing the Research through a Vygotskian Lens - Bethani Hoelzeman; Vicki S Collet (Educational Considerations, 2025)
Disciplinary literacy research at the secondary education level is prevalent, with some using sociocultural theory to frame adolescents’ acquisition of disciplinary literacies. Though existing research demonstrates potential benefits of incorporating disciplinary literacies in kindergarten through second grade, extant research at this level is minimal and undertheorized. This article illustrates present and potential connections to Vygotskian perspectives in this literature and offers an expanded theoretical framework for considering this work. Existing research on disciplinary literacies in kindergarten through second grade is analyzed, followed by a discussion of sociocultural practices that are present but undertheorized: using language and literacy as tools for learning, inquiry-based learning, collaborative learning, and disciplinary communities of practice. Then, drawing from tenets of Vygotskian theory, additional sociocultural concepts absent in the current literature are discussed–obuchenie, prolepsis, the social situation of development, and mediated play. Enlarging sociocultural theoretical connections could enhance research designs, methods, analyses, and reported outcomes and support meaningful enrichment of disciplinary literacies teaching and learning in the early grades.
Keywords: Disciplinary literacies; literacy; early childhood; elementary